Cross-examination of photoinitiated carrier and structural dynamics of black phosphorus at elevated fluences - Chebl, Mazhar; He, Xing; Yang, Ding-Shyue (The Journal of chemical physics, 2024)
Revived attention in black phosphorus (bP) has been tremendous in the past decade. While many photoinitiated experiments have been conducted, a cross-examination of bP's photocarrier and structural dynamics is still lacking. In this article, we provide such analysis by examining time-resolved data acquired using optical transient reflectivity and reflection ultrafast electron diffraction, two complementary methods under the same experimental conditions. At elevated excitation fluences, we find that more than 90% of the photoinjected carriers are annihilated within the first picosecond (ps) and transfer their energy to phonons in a nonthermal, anisotropic fashion. Electronically, the remaining carrier density around the band edges induces a significant interaction that leads to an interlayer lattice contraction in a few ps but soon diminishes as a result of the continuing loss of carriers. Structurally, phonon-phonon scattering redistributes the energy in the lattice and results in the generation of out-of-plane coherent acoustic phonons and thermal lattice expansion. Their onset times at ∼6 ps are found to be in good agreement. Later, a thermalized quasi-equilibrium state is reached following a period of about 40-50 ps. Hence, we propose a picture with five temporal regimes for bP's photodynamics.